Pengaruh Kepemilikan Manajerial, Kepemilikan Asing, dan Likuiditas terhadap Pengungkapan Laporan Keberlanjutan - Fatihah, Inggit Ukhti; Unggul Purwohedi; Etty Gurendrawati (LPPM Universitas Negeri Jakarta, 2023)
The purpose of this study is to analyze and test the influence of managerial ownership, foreign ownership, and liquidity on the disclosure of sustainability reporting, this study was conducted on non-financial companies listed on the Indonesia Stock Exchange for the period 2020-2021. The purposive sampling method was used as a sampling technique with 52 selected companies from all non-financial companies listed on the Indonesia Stock Exchange in 2020-2021. The data is processed by regression analysis of panel data with the Eviews 12 program. The results of this study show that foreign ownership and liquidity have a significant effect on the disclosure of sustainability reports. While managerial ownership has no effect whatsoever on the disclosure of sustainability reports.